Agência de Defesa Agropecuária do Estado do Pará - ADEPARÁ : Ações no Controle da Raiva dos Herbívoros. - Souza, Gildielle Bezerra Alexandrino de (Universidade Federal do Tocantins, 2023)
The supervised training course was held at the Agricultural Defense Agency of the State of Pará - ADEPARÁ, during the period from 03/13/2007 to 05/19/2017, with a workload of 400 hours, under the supervision of the Veterinary Doctor Ana Paula Backman, in the area of animal defense, in the Epidemiological Studies and Agricultural and Livestock Emergency - GEEPI. All the services developed by the sector were monitored. Among the health programs, there was active participation, especially in the State Program for the Control of Rabbits of Herbivores - PECRH, accompanying a suspected case of rabies and the stages of control and prevention. The Ministry of Livestock and Supply - MAPA is the highest body in the country that regulates all the processes of combating the main diseases in the production animals, with regard to animal health, regarding the prevention of zoonoses, coming from these animals and the Agencies of State Agricultural Defense are the executing agencies of these programs, obeying the current legislation. Because rabies is a viral disease of major importance for animal and human health, with mortality around 100% and having been the best-followed program during the internship, it was the theme chosen for the description in this report.